Discovery of a novel alphavirus related to Eilat virus - Hermanns, Kyra; Zirkel, Florian; Kopp, Anne; Marklewitz, Marco; Rwego, Innocent B; Estrada, Alejandro; Gillespie, Thomas R; Drosten, Christian; Junglen, Sandra (Journal of general virology, 2017)
Most alphaviruses are transmitted by arthropods and infect vertebrate hosts. An exception is Eilat virus (EILV), the only described alphavirus with a host range restricted to insects. We established a new generic reverse transcription PCR assay for alphaviruses and tested 8860 tropical mosquitoes. We detected a novel alphavirus, tentatively named Taï Forest alphavirus (TALV), in Culex decens mosquitoes collected in Ivory Coast. The full genome was sequenced, and closest similarity was found to EILV. Pairwise amino acid identities to EILV ranged between 67 and 88 % for the corresponding proteins, suggesting that TALV defines a proposed new alphavirus species. Phylogenetic analyses placed TALV as a sister species to EILV with a basal relationship to the western equine encephalitis virus complex. In comparison to the highly abundant insect-specific flaviviruses, insect-specific alphaviruses seem to be rare. This new PCR assay can detect novel alphaviruses and may facilitate the identification of additional new alphaviruses.